Commercial Local Pharmacotherapeutics and Adjunctive Agents for Nonsurgical Treatment of Periodontitis: A Contemporary Review of Clinical Efficacies and Challenges - Oi Leng Tan; Syarida Hasnur Safii; Masfueh Razali (MDPI AG, 2019)
Periodontal infections tend to be site-specific, mostly confined to the periodontal pocket. With the surge of antibiotic-resistant bacteria, the trend is shifting towards other therapeutic modalities, especially locally delivered approaches that include other pharmacotherapeutic drugs and medical devices. This narrative review aimed to provide insights into the clinical efficacy of local drug delivery and adjunctive agents used in nonsurgical management of periodontitis. Electronic (PubMed/MEDLINE, CENTRAL, and EMBASE) and bibliographic searches of past systematic reviews were carried out to identify previous publications on the topic. Only relevant literature and randomized controlled trials published in English were selected. In addition, a literature review was developed based on the selected articles. Experimental drugs or agents were excluded. This review highlights the clinically proven and commercially available therapeutic agents related to the management of periodontal disease with comparisons of their clinical efficacies and challenges. A vast array of commercial local pharmacotherapeutic agents had been clinically tested, but the methodologies and clinical results varied within and between each agent used, causing difficulty in drawing conclusions and providing support to the superiority of one agent over another. Considering the benefit−cost ratio with the modest clinical results, the long-term usefulness of these agents remains debatable.